A Assessment of the Level of Implementation Early Childhood Education Policy in Obubra Local Government of Cross River State, Nigeria: The Case Study of Cross River State Child Rights Act Policy - Ogundare, Olusegun; Ahmed, Hussein (African Journal of Behavioural and Scale Development Research, 2024)
This research was carried out to assess the level of implementation of policies regarding to early childhood education in obubra local government as enshrined in the Cross River State Child Rights Act Policy. A sample of 100 respondents completed the questionnaire designed for the study. The questionnaire sought information on the view of respondents about the implementation of early childhood education and how parents understand the concept and government efforts towards children with special needs. Data obtained from respondents were subjected to statistical analysis using percentages and mean. Results showed that respondents agree that early childhood education is necessary. It was also observed that there are inadequate facilities for children with special needs. The study also revealed that many parents are not familiar with the National Policy on Education hence they do not aware the section that prohibited children from hawking on the street or engage in domestic house help when they are expected to be in school learning. It was therefore recommended that government should go beyond making policies but enacting a law to make it mandatory for all children to go through early childhood education.